Uso de sensores inerciais portáteis para a avaliação de variáveis espaço-temporais da marcha em crianças: revisão sistemática - Fonseca Junior, Paulo Roberto (2018)
Background: Gait analysis is an important tool in the clinical evaluation of growing children with motor impairment. Objectives: The aim of the present study was to perform a literature review on the use wearable inertial sensors for gait analysis of children in clinical practice. Methods: Searches were performed in the MEDLINE, EMBASE, Cochrane Library and PEDro databases for studies involving children or adolescents submitted to gait analysis with the use of wearable inertial sensors. No restrictions were imposed regarding the date of publication or language. Results: Three hundred twenty articles were retrieved, 15 of which met the eligibility criteria, demonstrated adequate methodological quality and were selected for the present systematic review. Conclusion: The findings suggest that wearable sensors are effective for the evaluation of quantitative gait variables in children with different pediatric conditions, enabling an objective analysis that should prove useful in processes of clinical diagnosis and rehabilitation